EXPLORING THE COMPARATIVE TYPOLOGY OF GRAMMAR FORMS AND MEANINGS OF VERB TENSES - M.Nasimova; N.Shomamatova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Understanding verb tenses is fundamental to mastering any language. From indicating the time of an action to expressing its duration and completion, verb tenses play a crucial role in communication. However, the complexity of verb tense systems varies across languages, leading to intriguing differences in their grammar forms and meanings. In this article, we delve into the comparative typology of grammar forms and meanings of verb tenses across different languages, shedding light on how these variations influence language learning and usage.